2018
DOI: 10.1186/s13613-018-0439-x
|View full text |Cite
|
Sign up to set email alerts
|

Renal failure in critically ill patients, beware of applying (central venous) pressure on the kidney

Abstract: The central venous pressure (CVP) is traditionally used as a surrogate of intravascular volume. CVP measurements therefore are often applied at the bedside to guide fluid administration in postoperative and critically ill patients. Pursuing high CVP levels has recently been challenged. A high CVP might impede venous return to the heart and disturb microcirculatory blood flow which may cause tissue congestion and organ failure. By imposing an increased “afterload” on the kidney, an elevated CVP will particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 63 publications
1
53
0
Order By: Relevance
“…Elevated CVP correlated with AKI as corroborated by a meta-analysis done by Chen et al 11 Central venous pressure did not normalize in those patients with AKI resolution showing CVP trend might not truly reflect the clinical picture because of its limitations, and possibly also because different patients may have different levels of tolerance of CVP, whereas Doppler flow markers may better reflect the severity of organ congestion and potential dysfunction. Peripheral signs of fluid overload did not correlate with AKI, which reemphasizes the fact that they might not truly reflect the intravascular volume status.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Elevated CVP correlated with AKI as corroborated by a meta-analysis done by Chen et al 11 Central venous pressure did not normalize in those patients with AKI resolution showing CVP trend might not truly reflect the clinical picture because of its limitations, and possibly also because different patients may have different levels of tolerance of CVP, whereas Doppler flow markers may better reflect the severity of organ congestion and potential dysfunction. Peripheral signs of fluid overload did not correlate with AKI, which reemphasizes the fact that they might not truly reflect the intravascular volume status.…”
Section: Discussionmentioning
confidence: 86%
“… 10 A case series published by Denault et al on post-cardiac surgery patients showed portal vein Doppler assessment to be a promising modality for end-organ venous congestion in post-cardiac surgery patients. 11 Portal vein is subjected to variation because of body habitus and intrathoracic pressure. 12 , 13 …”
Section: B Ackgroundmentioning
confidence: 99%
“…Based on the rationale provided by the Starling curves and Guyton theory on cardiac function [4], high CVP may impede venous return to the heart and disturb microcirculatory blood flow which may harm organ function, lead to poor prognosis, and even increase mortality. Moreover, elevated CVP will particularly harm kidney hemodynamic and promote acute kidney injury (AKI) by imposing an increased "afterload" on the kidney [5]. However, the association between CVP and mortality and AKI in critically ill patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment for severe tricuspid regurgitation may occasionally be delayed until the onset of right‐sided heart failure with end‐organ damage. Elevated central venous pressure secondary to right‐sided heart failure leads to chronic renal failure, which consequently increases perioperative mortality 7,8 . In our opinion, in the present case, chronic end‐organ damage and right‐sided heart failure contributed to postoperative hemodynamic, respiratory, and renal deterioration.…”
Section: Discussionmentioning
confidence: 56%